Biology ContributionsHigh-dose-rate and pulsed-dose-rate brachytherapy for oral cavity cancer and oropharynx cancer - Polo, Alfredo (Journal of Contemporary Brachytherapy, 2009)
Interstitial brachytherapy represents the treatment of choice for small tumours, regionally localized in the oral cavity and the oropharynx. In the technical setting, continuous low-dose-rate (LDR) brachytherapy represented for many years the gold standard for administering radiation in head and neck brachytherapy. Large series of head and neck cancer patients treated with LDR brachytherapy have been reported, constituting an invaluable source of clinical data and the gold standard to compare results of new techniques. Nowadays, LDR brachytherapy competes with fractionated HDR and hyperfractionated PDR. In the paper an overview of the different time-dose-fraction alternatives to LDR brachytherapy in head and neck cancer is presented, as well as the radiobiological basis of different dose-rate schedules, the linear-quadratic model, interconversion of fractionation schedules and the repair half-times for early- and late-responding tissues. In subsequent sections essentials of switching from LDR to HDR and from LDR to PDR are discussed. Selected clinical results using HDR and PDR brachytherapy in oral cavity and oropharynx cancer are presented.